Resuscitation goals in septic shock: fluid therapy and vasoactive drugs, an integrative review - Sandro Guimarães Viveiros Rosa; Galo Guillermo Farfán Cano (School of Medicine, Universitas Syiah Kuala, 2023)
Severe sepsis and septic shock are complex syndromes with high mortality that frequently affect ICU patients. Contributions such as the Surviving Sepsis campaign have led to the issuing of guidelines for managing these patients. This manuscript aims to provide a review of state of the art using a systematic review of resuscitation and the use of vasopressors in patients with septic shock. Using MESH terms and Boolean operators, systematic research for information was carried out in PubMed in February 2023. We included 28 articles of which 18 were selected using the prism algorithm that met the inclusion criteria (analysis of septic shock, fluid resuscitation, or the use of vasopressors in septic shock in humans). In conclusion, the management of septic shock should be performed based on clear objectives to improve outcomes, for which maintenance of physiological levels of oxygenation, serum lactate, and mean arterial blood pressure are crucial.